Cemented total hip arthroplasty with retention of some existing hardware - Judas, F (2014)
We report a case of a 63-year-old man who presented an end stage hip osteoarthritis 42 years after a proximal femoral osteotomy performed for the treatment of an intracapsular femoral neck fracture. A cemented total hip arthroplasty was implanted using a standard posterior approach. The osteotomy hardware was totally covered with a new cortical bone formation. A layer of bone tissue was removed, the screw heads were broken and the nail plate was also removed. The screw threaded portions were retained because they did not interfere with cemented femoral stem implantation. Fourteen years after total hip arthroplasty, the patient reported no pain and expressed high satisfaction with the surgery. The hip radiograph showed wear of the polyethylene cup and no periprosthetic osteolysis. Retention of hardware can be considered, especially in patients who have had hardware for several years, without any negative symptoms.